1998
DOI: 10.1212/wnl.51.6.1532
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment in abstinent MDMA ("Ecstasy") users

Abstract: Abstinent MDMA users have impairment in verbal and visual memory. The extent of memory impairment correlates with the degree of MDMA exposure and the reduction in brain 5-HT, as indexed by CSF 5-HIAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
254
2
5

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(288 citation statements)
references
References 14 publications
27
254
2
5
Order By: Relevance
“…It indicates that MDMA's effect on spatial memory is not due to its action within the dopaminergic system. Though MDMA exerts its effects in the brain through a multitude of transmitter systems, it is generally assumed that MDMA induced memory deficits that are related to changes in serotonergic function (Bolla et al 1998;McCann et al 1994;Reneman et al 2002;Verkes et al 2001). The present data seem to support this general notion.…”
Section: Discussionmentioning
confidence: 99%
“…It indicates that MDMA's effect on spatial memory is not due to its action within the dopaminergic system. Though MDMA exerts its effects in the brain through a multitude of transmitter systems, it is generally assumed that MDMA induced memory deficits that are related to changes in serotonergic function (Bolla et al 1998;McCann et al 1994;Reneman et al 2002;Verkes et al 2001). The present data seem to support this general notion.…”
Section: Discussionmentioning
confidence: 99%
“…Improved impulse control during serotonergic suppletion seems in line with reports on impaired impulse control in heavy users of MDMA during periods of abstinence. Studies on serotonergic function in recreational MDMA users have repeatedly shown low levels of 5HIAA in CSF (Bolla et al, 1998;McCann et al, 1994;Peroutka et al, 1987;Ricaurte et al, 1990), reduced density of 5-HT transporters (Reneman et al, 2002) and blunted neuro-endocrine responses in serotonergic challenge tests (Gerra et al, 1998;McCann et al, 1999;Verkes et al, 2001) when compared to nondrug using controls. In addition, serotonergic depletion has been linked to behaviors characterized by impaired impulse control (Linnoila et al, 1983(Linnoila et al, , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction 3,4-Methylenedioxymethamphetamine (MDMA, 'ecstasy') is widely used as a recreational drug by young people despite having been shown to be a neurotoxin in the brains of rodents and non-human primates (Green et al 2003) and to produce lasting specific memory deficits in humans (Bolla et al 1998;Verkes et al 2001;Fox et al 2002;Verbaten 2003;Soar et al 2004;Wareing et al 2000;2004a,b;Montgomery et al 2005;Gouzoulis-Mayfrank et al 2003. These psychopathological disturbances are probably a consequence of the long-term neurochemical changes induced by the drug (Reneman et al 2000;Cowan et al 2003;Daumann et al 2005).…”
mentioning
confidence: 99%